SET DECIPHERABLE LANGUAGES AND GENERATORS - Duc, Tran Vinh (Journal of Computer Science and Cybernetics, 2020)
We investigate the problem to characterize whether the infinite product of a given language $L$ is generated by an $ω$-code. Up to now, this problem is open even if language $L$ is a finite language.In this work, we consider a class of languages named $ω$-set decipherable languages which are very close to the $ω$-codes. We solve the problem in the restricted case where $L$ is $ω$-set decipherable and $L^*$ is the greatest generator of $L^ω$.